2010
DOI: 10.3109/0142159x.2010.490282
|View full text |Cite
|
Sign up to set email alerts
|

Reassuring the medical students’ disease – Health related anxiety among medical students

Abstract: Background: Studying a specific illness could lead medical students to an incorrect interpretation of certain physical symptoms, so that symptoms which were previously considered normal are now regarded as a true sign of an illness. Aim: To examine the appraisal of self-health state, the existing fear of morbidity and the level of health-related anxiety among medical students throughout medical school. Methods: Anonymous questionnaires were distributed to first through sixth year medical students at the Tel-Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
1
27
1
5
Order By: Relevance
“…Additional correlation of the falsehood-items with the BDI-II items demonstrated no link. An explanation of the finding might be the so-called “medical students’ disease” [ 42 ], an incorrect interpretation of certain physical symptoms and a normal phenomenon especially in the early phase of medical training. It is acceptable that this is also the case in students of physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additional correlation of the falsehood-items with the BDI-II items demonstrated no link. An explanation of the finding might be the so-called “medical students’ disease” [ 42 ], an incorrect interpretation of certain physical symptoms and a normal phenomenon especially in the early phase of medical training. It is acceptable that this is also the case in students of physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Azuri et al [16] noted a significant prevalence of psychosomatic disorder when enrolling for clinical posting with a significant decrease later on. Furthermore, in one Australian study, the prevalence of somatization among Australian general practitioners revealed a higher prevalence of 18.6% which is more than that seen in our study [17].…”
Section: Discussionmentioning
confidence: 99%
“…As participants in the current study were a specific non-health seeking sample, more diverse samples and including clinical samples would need to be used to establish the generalizability of the factor structure and reliability of the measure. However, as noted health anxiety is normally distributed in student groups generally (Marcus et al, 2008) and medical based students specifically (Azuri, Ackshota, & Vinker, 2010;Zhang et al, 2014). …”
Section: A Measure Of Metacognitive Beliefs In Health Anxiety 14 14mentioning
confidence: 96%